PENGARUH PENGEMBANGAN KARIR DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN PT. JOHAN SENTOSA BANGKINANG - Astrika, Cici; ', Zulfadil; ', Haryetti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine how the influence of career development and work environments simultaneously and partially on employee job satisfaction PT. Johan Sentosa Bangkinang. The population at this study were employees at PT. Johan Sentosa Bangkinang which amounted to 51 people. While the sampling are all employees. Analysis of the data used is descriptive and multiple linear regression. The types and sources of data used are primary and secondary data. Hipotesis tests indicated that, simultaneously the career development and working environment have a significant effect on employee job satisfaction, while the partial test both career development and working environment have a significant effect on employee job satisfaction. It is expected companies to improve employee job satisfaction by providing promotional opportunities for all employees who meet certain standards. With the implementation of the terms of expected employees will be motivated to achieve corporate goals. Expected to companies that seek to improve employee job satisfaction by providing provide promotional opportunities for all employees who meet certain standards, such as employees who have been working and the employees who have performed above average or very maximum.Keyword : Career Development, Work Environments and Job Satisfaction